Ribonuclease H‐like gene SMALL GRAIN2 regulates grain size in rice through brassinosteroid signaling pathway. Issue 10 (14th September 2022) - Huang, Yunshuai; Dong, Hui; Mou, Changling; Wang, Ping; Hao, Qixian; Zhang, Min; Wu, Hongmin; Zhang, Fulin; Ma, Tengfei; Miao, Rong; Fu, Kai; Chen, Yaping; et al.
ABSTRACT: Grain size is a key agronomic trait that determines the yield in plants. Regulation of grain size by brassinosteroids (BRs) in rice has been widely reported. However, the relationship between the BR signaling pathway and grain size still requires further study. Here, we isolated a rice mutant, named small grain2 ( sg2 ), which displayed smaller grain and a semi‐dwarf phenotype. The decreased grain size was caused by repressed cell expansion in spikelet hulls of the sg2 mutant. Using map‐based cloning combined with a MutMap approach, we cloned SG2, which encodes a plant‐specific protein with a ribonuclease H‐like domain. SG2 is a positive regulator downstream of GLYCOGEN SYNTHASE KINASE2 (GSK2) in response to BR signaling, and its mutation causes insensitivity to exogenous BR treatment. Genetical and biochemical analysis showed that GSK2 interacts with and phosphorylates SG2. We further found that BRs enhance the accumulation of SG2 in the nucleus, and subcellular distribution of SG2 is regulated by GSK2 kinase activity. In addition, Oryza sativa OVATE family protein 19 (OsOFP19), a negative regulator of grain shape, interacts with SG2 and plays an antagonistic role with SG2 in controlling gene expression and grain size. Our results indicated that SG2 is a new component of GSK2‐related BR signaling response and regulates grain size by interacting with OsOFP19. Abstract : The rice Ribonuclease H‐like gene SMALL GRAIN2 ( SG2 ) positively regulates grain size via the brassinosteroid signaling pathway. SG2 is a positive regulator downstream of GLYCOGEN SYNTHASE KINASE2 (GSK2) in regulating brassinosteroid responses. GSK2 interacts with and phosphorylates SG2 and regulates the subcellular distribution of SG2.